Comparative study of biosynthesis technology and traditional methods for organic solid waste - Wang Yuzhou (E3S Web of Conferences)
With the development of industrialization and trade, the amount of organic solid waste is increasing rapidly, which has a serious impact on the environment. Traditional methods of organic solid waste treatment method will have negative impacts during the process of the treating organic solid waste. The theme of the study is to find an efficient, environmentally friendly and economical organic solid waste treatment method. The best organic sold waste treatment method is determined by comparing landfill, incineration and biosynthesis technology in aspects of resource utilization, cost and environmental impact. Through research, in aspects of resource utilization and cost, biosynthesis technology has its own advantages and disadvantages compared with traditional landfill and incineration technologies. In aspects of environmental impact, biosynthesis technology has obvious advantages. This is not only because of the mild reaction conditions and no secondary pollutants of biosynthesis technology, but also because biosynthesis technology can improve the soil condition and reduce the emission of the greenhouse gas.